2019
DOI: 10.1108/nfs-02-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food additives and cooking on the antioxidant properties of purslane

Abstract: Purpose This paper aims to study the effect of cooking and food additives, such as lemon juice and vinegar, on phenols and flavonoids contents and antioxidant activity of purslane. Design/methodology/approach The Folin–Ciocalteu method was used to determine total phenols content (TP), while total flavonoid content (TF) was determined by the aluminum chloride method. Two methods were used for determination of antioxidant activity: DPPH (1, 1-diphenyl-2-picrylhydrazyl) assay to determine radical scavenging act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a previous work comparing the raw, boiled, and blanched P. oleracea , it was observed that the raw sample had a higher TPC value (23 mg GAE/g DE) compared to the values of the cooked samples (boiled 19 mg GAE/ g DE and blanched 10 mg GAE/g DE) [ 23 ]. In another study, Naser Aldeen et al obtained slightly higher values for cooked than raw purslane (13.13 mg GAE/g DE and 12.75 mg GAE/g DE, respectively) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work comparing the raw, boiled, and blanched P. oleracea , it was observed that the raw sample had a higher TPC value (23 mg GAE/g DE) compared to the values of the cooked samples (boiled 19 mg GAE/ g DE and blanched 10 mg GAE/g DE) [ 23 ]. In another study, Naser Aldeen et al obtained slightly higher values for cooked than raw purslane (13.13 mg GAE/g DE and 12.75 mg GAE/g DE, respectively) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previously reported value in an ABTS assay for raw purslane was 102.7 µmol TE/g DE, lower than that obtained in our study [ 43 ]. In another work on aerial parts of Portulaca oleracea , the cooking process with lemon juice as additive increased the antioxidant activity compared to raw samples in the DPPH assay [ 24 ]. The decrease in antioxidant activity observed after the steaming process is in agreement with the decrease in phenolic content ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other valuable components of purslane edible parts include minerals, such as calcium, potassium and phosphorus, macronutrients such as proteins and carbohydrates [5], as well as tocopherols, carotenoids and ascorbic acid [6,7]. Moreover, phenolic compounds and oleracein derivatives of extracts of purslane leaves have been attributed with antioxidant properties [8], while their content may be affected by cooking and food additives [9]. P. oleracea is tolerant under stress conditions, such as heat, drought and salinity stress, a trait that could be useful within the ongoing climate change context and provide alternative solutions to farmers in climate-affected regions [10].…”
Section: Introductionmentioning
confidence: 99%